Sistim pemerintahan Pantja Sila - Kartohadiprodjo, Soediman, 1908-1970 (Bandung : Badan Pembina Djiwa Kekeluargaan Mahasiswa Fakultas Hukun Universitas Katolik Parahyangan, 1967)
Democracy based on Pantjasila.
Keywords: Indonesia -- Politics and government